Alternative or cytochrome? Respiratory pathways in traps of aquatic carnivorous bladderwort Utricularia reflexa - Pavlovič, Andrej; Jakšová, Jana; Hrivňacký, Martin; Adamec, Lubomír (Plant signaling & behavior, 2022)
Carnivorous plants of the genus Utricularia (bladderwort) form modified leaves into suction bladder traps. The bladders are metabolically active plant tissue with high rates of mitochondrial respiration (RD). In general, plants possess two mitochondrial electron transport pathways to reduce oxygen to water: cytochrome and an alternative. Due to the high metabolic rate in the bladders, it is tempting to assume that the bladders prefer the cytochrome c oxidative pathway. Surprisingly, we revealed that alternative oxidase (AOX), which yields only a little ATP, is much more abundant in the bladders of Utricularia reflexa in comparison with the shoots. This pattern is similar to the carnivorous plants with passive pitcher traps (e.g. Sarracenia, Nepenthes) and seems to be widespread across many carnivorous taxa. The exact role of AOX in the traps of carnivorous plants remains to be investigated.
Keywords: Cytochromes c; Plant Leaves; cytochromy c; Alternative oxidase; Oxygen; carnivorous plants; adenosintrifosfát; kyslík; Water; Adenosine Triphosphate; cytochrome c oxidase; light harvesting antennae; respiration; bladderwort; voda; listy rostlin